Endothelial Dysfunction and Hyperhomocysteinemia-Linked Cerebral Small Vessel Disease: Underlying Mechanisms and Treatment Timing - Li, Shuang; Li, Guangjian; Luo, Xia; Huang, Yan; Wen, Lan; Li, Jinglun (Frontiers in Neurology, 2021)
Cerebral small vessel disease (cSVD)—a common cause of stroke and vascular dementia—is a group of clinical syndromes that affects the brain’s small vessels, including arterioles, capillaries, and venules. Its pathogenesis is not fully understood, and effective treatments are limited. Increasing evidence indicates that an elevated total serum homocysteine level is directly and indirectly associated with cSVD, and endothelial dysfunction plays an active role in this association. Hyperhomocysteinemia affects endothelial function through oxidative stress, inflammatory pathways, and epigenetic alterations at an early stage, even before the onset of small vessel injuries and the disease. Therefore, hyperhomocysteinemia is potentially an important therapeutic target for cSVD. However, decreasing the homocysteine level is not sufficiently effective, possibly due to delayed treatment, which underlying reason remains unclear. In this review, we examined endothelial dysfunction to understand the close relationship between hyperhomocysteinemia and cSVD and identify the optimal timing for the therapy.